2015
DOI: 10.3189/2015jog14j095
|View full text |Cite
|
Sign up to set email alerts
|

Marine ice recycling at the southern McMurdo Ice Shelf, Antarctica

Abstract: Marine ice accretes at the base of ice shelves, often infilling open structural weaknesses and increasing ice-shelf stability. However, the timing and location of marine ice formation remain poorly understood. This study determines marine ice source water composition and origin by examining marine ice crystal morphology, water isotope and solute chemistry in ice samples collected from the southern McMurdo Ice Shelf (SMIS), Antarctica. The measured co-isotopic record together with the output of a freezing model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 77 publications
1
18
0
Order By: Relevance
“…The smooth band along the marine ice exposure has a similar density, although appearing with an albedo that is indiscernible from the snow-covered part of the ice-shelf on satellite imagery. We interpret this band as marine ice covered by a thin veneer of possibly seasonal and/or wind-blown snow, which is supported by in field ground-based radar and ice sample evidence (Koch, 2016). It can also be shown that the limit of the snow-covered part of SMIS can reach further north on Landsat images and varies seasonally.…”
Section: Marine-to-meteoric Ice Transitionsupporting
confidence: 80%
See 2 more Smart Citations
“…The smooth band along the marine ice exposure has a similar density, although appearing with an albedo that is indiscernible from the snow-covered part of the ice-shelf on satellite imagery. We interpret this band as marine ice covered by a thin veneer of possibly seasonal and/or wind-blown snow, which is supported by in field ground-based radar and ice sample evidence (Koch, 2016). It can also be shown that the limit of the snow-covered part of SMIS can reach further north on Landsat images and varies seasonally.…”
Section: Marine-to-meteoric Ice Transitionsupporting
confidence: 80%
“…This argument is supported by the known exposure of marine ice at the ice-shelf surface within the adjacent EF1. Such a setting accommodates the ice-shelf vertical structure proposed by Koch (2016) from ground radar observations. In that scenario, the slope break in the basal reflector delimiting SMIS2 from SMIS3 (Fig.…”
Section: Basal Unitsmentioning
confidence: 93%
See 1 more Smart Citation
“…The larger maximum, peak A, likely originates from the confluence of the McMurdo and Ross Ice Shelves (Robinson et al, 2014) as 565 indicated by the arrow north of Black Island in Figure 11. Alternatively, marine ice has been found in the southern McMurdo Ice Shelf (Koch et al, 2015;Grima et al, 2019) and a possible additional source may emerge from the channel between Black Island and the Brown Peninsula (see Figure 1a and 11). Once it emerges from under the ice shelf and spreads out under the fast ice, this stream moves westward under the influence of the Coriolis force (Robinson et al, 2014) as modelled by Cheng et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The AIS is not the only ice shelf with a marine ice layer. Marine ice layers have also been recorded beneath the Filcher‐Ronne, Ross, Hells Gate, Nansen, and southerm McMurdo ice shelves [e.g., Gow , ; Zotikov et al ., 1980; Souchez et al , ; Oerter et al , ; Eicken et al , ; Tison et al , ; Khazendar et al , ; Lambrecht et al , ; Koch et al , ], and suggested beneath the West Ice Shelf [ Warren et al , ]. This list does not preclude marine ice layers in other less studied ice shelves.…”
Section: The Amery Ice Shelf and The Formation Of The Marine Ice Layermentioning
confidence: 99%